P II – 1–6 A critical analysis of the drivers of human migration patterns in the presence of contemporary climate change: presentation of a new conceptual model. (18th March 2018) - Parrish, Rebecca; Zeka, Ariana; Colbourn, Tim; Lauriola, Paolo; Hajat, Shakoor; Leonardi, Giovanni
Abstract : Background/aim: Climate change can both directly and indirectly drive human migration. Despite this, strong understanding of the system of determinants of migration and their interactions, remains a knowledge gap resulting in large uncertainties and ill-informed interventions. Objectives: To create a new conceptual model for the identification of drivers of migration in the context of climate change. Methods: A critical analysis of existing theoretical and quantitative literature was performed in order to synthesise a new conceptual model for identifying the migration determinants system. Results: Quantitative studies fail to homogenously apply a theoretical model for the drivers of migration and the variety of migration outcomes that occur. This in turn results in a poor evidence-base for interventions in areas where this is critical, including public health, land planning and immigration policies. Existing theoretical models are insufficiently transferable and fail to capture the full range of migration determinants. A new migration typology and conceptual model of migration is constructed based on an upstream, holistic approach to migration. The model overcomes current shortcomings by capturing temporality and driver dynamics as well as being a plastic model that may be transferred into any context. Conclusion: From the homogenous application of such a conceptual framework, quantitative models may also be able to more accurately quantify the extent to which contemporary and future climate change influences migration. Such models are therefore informative tools for decision-making concerning strategies for migration policy and public health planning.